Koordinasi Penanganan Bencana Melalui Aplikasi E-Laporbencana Antara BPBD Provinsi Kalimantan Barat dengan Masyarakat - Muhammad Aqila Bagastomo aqila; Lulu Agusti Aulia lulu; Maychel yoas pandapotan sinaga maychel; Dwi Ahmad Mussofa dwi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
west kalimantan is one of the provinces with many disasters. for this reason, in handling disasters, the government must address it through the regional disaster management agency (bpdb) of west kalimantan province. in 2019, there was a significant increase in the number of disasters. the most increasing disaster is forest fires. if the disaster complaint is still in the conventional stage (without involving the information system), this complaint can be made by coming directly to the bpbd office or sending a letter to the address of the office. in 2019 there were many problems faced by bpbd. some of them are the slow reporting of disaster events and the lack of adequate information. of course, this can be handled by sending data and information quickly via e-disaster reports. the hope is that with the speedy delivery of this information, decisions and coordination with the community can be carried out quickly and precisely.